Epitaxial Growth of Large‐Grain NiSe Films by Solid‐State Reaction for High‐Responsivity Photodetector Arrays. Issue 17 (1st March 2017) - Cai, Caoyuan; Ma, Yang; Jeon, Jaeho; Huang, Fan; Jia, Feixiang; Lai, Shen; Xu, Zhihao; Wu, Congjun; Zhao, Ruiqi; Hao, Yufeng; Chen, Yiqing; Lee, Sungjoo; et al.
Abstract : Film‐based photodetectors have shown superiority for the fabrication of photodetector arrays, which are desired for integrating photodetectors into sensing and imaging systems, such as image sensors. But they usually possess a low responsivity due to low carrier mobility of the film consisting of nanocrystals. Large‐grain semiconductor films are expected to fabricate superior‐responsivity photodetector arrays. However, the growth of large‐grain semiconductor films, normally with a nonlayer structure, is still challenging. Herein, this study introduces a solid‐state reaction method, in which the growth rate is supposed to be limited by diffusion and reaction rate, for interface‐confined epitaxial growth of nonlayer structured NiSe films with grain size up to micrometer scale on Ni foil. Meanwhile, patterned growth of NiSe films allows the fabrication of NiSe film based photodetector arrays. More importantly, the fabricated photodetector based on as‐grown high‐quality NiSe films shows a responsivity of 150 A W −1 in contrast to the value of 0.009 A W −1 from the photodetector based on as‐deposited NiSe film consisting of nanocrystals, indicating a huge responsivity‐enhancement up to four orders of magnitude. It is ascribed to the enhanced charge carrier mobility in as‐grown NiSe films by dramatically decreasing the amount of grain boundary leading to scattering of charge carrier. Abstract : Non‐layer structured NiSe films with grain size up to micron scale have been epitaxially grown on Ni foil by solid‐state reaction. Patterned growth of NiSe films allows the fabrication of NiSe film based photodetector arrays with a responsivity of 150 A/W in contrast to 0.009 A/W from the device based on as‐deposited NiSe nanocrystal films.